Effectiveness of Structured Teaching Programme on Knowledge regarding Risk factors and Prevention of Suicidal Behaviour among Adolescents in a selected College, Salem, Tamil Nadu - Loganathan, N (Journal of College of Medical Sciences-Nepal, 2015)
Background & Objectives: The aim of this study is to assess the knowledge regarding risk factors and prevention of suicidal behavior, to evaluate the effectiveness of structured teaching programme on knowledge regarding risk factors and prevention of suicidal behaviour among Adolescents, and to associate the pre-test knowledge regarding risk factors and prevention of suicidal behaviour among adolescents with their selected demographic variables. Materials & Methods: A quantitative evaluative approach with a pre-experimental (one group pre test- post test) design was adopted; the setting of the study was Sri Vidya Mandir College, Salem, Tamilnadu. A Structured Self-administered questionnaire was used to assess the knowledge of the adolescents. The systematic random sampling technique was used and 60 adolescents involved on Structured Teaching Programme regarding Risk factors and prevention of Suicidal Behaviour by using a Power-point slide presentation followed with pre-test. On 7th day, the post test was conducted. The data collection period of the study was 09.12.2014 to 15.12.2014. Results: The study findings revealed that during Pre-test, the knowledge regarding risk factors and prevention of suicidal behaviour among adolescents, 45(75%) had inadequate knowledge, 15(25%) had moderately adequate knowledge and none of them had adequate knowledge. During post test, 23 adolescents (38.33%) had adequate knowledge, 37(61.67%) had moderately adequate knowledge and none of them had inadequate knowledge. The mean score during pre-test was 9.9±3.88 and the mean score during post test was 17.03±4.12. The paired ‘t’ value was 16.84 which were significant at p<0.05 level. Thus it shows that the structured teaching programme was effective in improving knowledge regarding risk factors and prevention of suicidal behaviour among adolescents. There was no significant association found between the pre-test scores on knowledge regarding risk factors and prevention of suicidal behaviour and the selected demographic variables at p<0.05 level. involved. Conclusion: The study concluded that the structured teaching programme was effective among adolescents to improve the knowledge regarding risk factors and prevention of suicidal behaviour. JCMS Nepal. 2015;11(3):25-29.